Body/Text/History: Violation of Borders in Assia Djebar's Fantasia - David Waterman (Studies in 20th & 21st Century Literature, 1998)
Assia Djebar's novel Fantasia: An Algerian Cavalcade (1985) can be read as a political novel which examines the permeability of borders, especially between Algeria and the female body. As the primary site of signification and meaning, the body becomes a text which attempts to circulate knowledge and encourage resistance outside a position of mastery, and the same body/text suffers as it is inscribed by the dominant power. The distinction between nature and culture is interrogated as the borders of the body/text overlap the borders of war, writing, history, and sexuality. Ultimately, given the position of the female body within the symbolic system, the border between war and peace is revealed as illusory.
Keywords: Body; Text; History; Assia Djebar; Fantasia: An Algerian Cavalcade; political novel; permeability of borders; borders; Algeria; female body; knowledge; resistance; dominant power; war; writing; history; sexuality; illusory